Determining significant leadership behaviors of active duty Air Force Chief Master Sergeants working on Randolph Air Force Base, Texas: a phenomenological inquiry - Machen II, Paul A. (Kansas State University, 2009)
To date, several academic studies have examined officer personnel leadership behaviors, while the leadership traits of enlisted personnel have largely been ignored. This dissertation investigates the leadership behaviors of active duty chief master sergeants (CMSgt) working on Randolph Air Force Base (AFB), Texas and offers conclusions concerning the acquisition of these behaviors. The main distinction between an officer and enlisted person is, enlisted did not have an undergraduate college degree when they first entered the Air Force. The enlisted population was selected because of the researcher’s background in the Air Force. The sample selection process consisted of obtaining a list from the Air Force of active duty CMSgts working on Randolph AFB. Next, several CMSgts were selected and asked to participate in the study. Those who chose to participate were asked if they knew of other CMSgts who could provide useful information for this study. Four of these participants were chosen to complete in the pilot study phase. Data was collected through the use of semi-structured interviews until thematic saturation was accomplished. Data analysis began with the first pilot interview and continued throughout all phases of this research study. This research found 12 significant leadership behaviors, which can be placed into eight categories. The eight categories are: Technical; Counselor; Problem-Solver; Manager; Networker; Communicate Vision; Eyes and Ears; Run Interference. The Technical category contains one sub-category: Assign Task / Communicate Expectations. The Counselor category is comprised of Influence, Supporter, and Facilitator, while the Manager category is made up of Decision Maker, Advisor, and Mentor.
Keywords: Leadership; Military; Behaviors; Enlisted; Air Force; Training; Education, Adult and Continuing (0516)